Understanding and addressing needs of community stroke survivors in a low resource setting: Improving outcomes for Rwandan stroke survivors - Kumurenzi, Anne (My University, 2023)
Stroke survivors in low-resource settings like Rwanda often face high levels of disability, and access to rehabilitation care is limited. To effectively allocate resources, it is crucial to understand and address the most significant concerns of stroke survivors and explore contextually appropriate approaches to post-stroke care. We conducted a needs assessment survey of 337 patients from six hospitals in Rwanda, collecting data at discharge and three months post-stroke. Rwandan stroke survivors have similar unmet functional needs as those in high-resource settings. However, over half of the participants still reported moderate to severe mobility, usual activities, and social/recreational activities needs at three months post-discharge. Stroke survivors indicate that limited access to services was a significant barrier to addressing these needs. Community-based interventions may be an important method for addressing these needs; however, rehabilitation services are limited, warranting the need to consider alternative strategies to address these needs. The thesis explores the potential of involving community health workers (CHWs) in providing rehabilitation interventions for stroke survivors in community settings. Although the effectiveness of CHWs in providing physical rehabilitation interventions in low-resource settings remains uncertain and sustainability of these interventions outside the studied context is also unclear. Subsequent the use of CHWs for post-stroke rehabilitation is a worthwhile endeavor. To facilitate the implementation of CHW-delivered interventions, two crucial steps were considered: the development of an intervention and establishing an operational team that will ensure implementation success. A multi-phased process was used to design a new evidence-informed post-stroke community-level mobility intervention suitable for low-resource settings. The Rehabilitation Treatment Specification System enabled the intervention design and description toward facilitating its accurate replication. The next step is to test the intervention’s feasibility, effectiveness, and implementation in low-resources settings.
Keywords: Stroke survivors; Needs; Low-resource setting; Rwanda